2011
DOI: 10.1186/1756-9966-30-117
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and treatment strategies in early gastric cancer: a retrospective cohort study

Abstract: BackgroundBoth endoscopic and surgical approaches are employed in the treatment of early gastric cancer (EGC). The aim of this study was to establish appropriate treatment strategies for early gastric cancer.MethodsWe retrospectively examined clinicopathological data of EGC patients who had undergone surgery.ResultsA total of 327 patients (204 males and 123 females, mean age 63.2 years) were eligible for inclusion in the study. The median follow-up period was 31 months. Of 161 mucosal (pT1a) tumors, 87 were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Similarly, EGCs with LNM were found to be more in submucosa invasion and LVI in our study. Besides them, tumor differentiation and histologic types have been demonstrated to predict the likelihood of LNM [ 28 , 29 ]. However, in our study, we failed to found significant differences in the rate of LNM among them, although this trend still existed.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, EGCs with LNM were found to be more in submucosa invasion and LVI in our study. Besides them, tumor differentiation and histologic types have been demonstrated to predict the likelihood of LNM [ 28 , 29 ]. However, in our study, we failed to found significant differences in the rate of LNM among them, although this trend still existed.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps one of the most striking yet unexpected findings is a high overall lymph node metastasis rate of 23%, which is much higher than that reported in Japanese series evaluating early small carcinomas (≤2 cm in size) with poor prognostic indicators (ulcerative gross appearance and undifferentiated carcinoma histology). 34 , 35 In general, the prognosis of PGCs is reported to be worse than that of DGCs. 4 , 36 38 This is directly related to the more advanced pT stage, as previously described in Korean and Chinese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the degree of cell differentiation, welldifferentiated tumors have a lower rate of metastasis than their moderately differentiated and poorly differentiated counterparts. Accordingly, as for Lauren's classification, the intestinal type tends to have a lower rate of lymph node metastasis than the diffuse one 26 . These data are confirmed in our work and can be seen in Table 5.…”
Section: T T T T Tmentioning
confidence: 93%